Industrial impact analysis of foreign direct investment on economic development in Cambodia - Sovath Kenh; Qidi Wei (Journal of Business and Socio-Economic Development)
Purpose – Cambodia's sustained and robust growth performance since the post-reform era in 1993 has been attributed to the boom in inward foreign direct investment (FDI) attracted to the country's labor-intensive industries, where it has comparative advantages. The purpose of this study is twofold. First, it aims to assess the consistency between Cambodia's revealed comparative advantage in exports and its sectoral inward FDI. Second, it examines the relationship between industry-level FDI and growth performance by accounting for heterogeneity across industries. Design/methodology/approach – The paper uses descriptive methods and an industry-level dataset provided by the Council for the Development of Cambodia to elucidate the issue. Additionally, it applies instrumental variable two-stage least squares (IV-2SLS) regression to investigate the impact of industry-specific FDI on economic growth from 1994 to 2017, which also aims to address the endogeneity issue. Findings – On the one hand, our research finds that Cambodia's FDI has been attracted to sectors in which it has a comparative advantage during the aforementioned period. On the other hand, both FDI and the comparative advantage index significantly impact economic growth in Cambodia. The greater the flow of foreign investment into sectors with comparative advantage, the stronger the impetus for growth. Originality/value – This study fills a gap in the literature and contributes to a better understanding of the relationship between FDI and economic growth in Cambodia. It is the first paper to investigate the heterogeneity of industry-specific FDI and provides practical recommendations for policymakers to effectively harness foreign investments and avoid malign FDI inflows.